An Extra‐Broadband VIS‐NIR Emitting Phosphor toward Multifunctional LED Applications (Adv. Funct. Mater. 7/2022). (8th February 2022) - Xiao, Yu; Xiao, Wenge; Wu, Dan; Guan, Linquan; Luo, Min; Sun, Ling‐Dong
Abstract : Broadband Emission In article number 2109618, Wenge Xiao, Ling‐Dong Sun, and co‐workers develop a visible–near‐infrared emitting phosphor based on the combination of the dual roles of Mn 2+ in generating red and near‐infrared emission and the energy transfer from Ce 3+ to Mn 2+ in Lu2 BaAl4 SiO12 garnet. Their study demonstrates that Mn 2+ with highly symmetric coordination can serve as an activator for designing near‐infrared phosphors.